2018
DOI: 10.1371/journal.pbio.2005099
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of mitotic spindle behavior during the first asymmetric embryonic division of nematodes

Abstract: Asymmetric cell division is essential to generate cellular diversity. In many animal cells, the cleavage plane lies perpendicular to the mitotic spindle, and it is the spindle positioning that dictates the size of the daughter cells. Although some properties of spindle positioning are conserved between distantly related model species and different cell types, little is known of the evolutionary robustness of the mechanisms underlying this event. We recorded the first embryonic division of 42 species of nematod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…In addition to developmental spindle scaling, correlations between embryo, cell, and spindle sizes have been characterized across a wide variety of different species (Crowder et al, 2015;Farhadifar et al, 2015;Valfort, Launay, Semon, & Delattre, 2018). X. laevis spindles are larger than Xenopus tropicalis spindles (Brown et al, 2007).…”
Section: Mitotic Spindlesmentioning
confidence: 99%
“…In addition to developmental spindle scaling, correlations between embryo, cell, and spindle sizes have been characterized across a wide variety of different species (Crowder et al, 2015;Farhadifar et al, 2015;Valfort, Launay, Semon, & Delattre, 2018). X. laevis spindles are larger than Xenopus tropicalis spindles (Brown et al, 2007).…”
Section: Mitotic Spindlesmentioning
confidence: 99%
“…Despite these conflicting results on bacterial aging, diverse studies have suggested asymmetric damage partitioning as a common mechanism of cell maintenance. Besides bacteria and yeast, the physiological asymmetry between daughter cells has been observed in diatoms 12 , nematodes 21 , stem cells 22 24 , and others. Thus, the identification of a deterministic divisional asymmetry in bacteria, leading to aging and rejuvenation in clonal populations, could further characterize aging at the cellular level as a ubiquitous process in living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…As the cell cycle progresses, unbalanced cortical forces shift the spindle towards a posterior location. However, other Caenorhabditis species with similar cellular shapes show anterior or posterior nuclear positions of the spindle at the onset of mitosis (Valfort et al ., ).…”
Section: Biophysical Factors Influence Asymmetric Stem Cell Divisionmentioning
confidence: 97%